Scleroderma yunnanense Y. Wang : a Gastroid Fungi New to Nepal - Mahesh Kumar Adhikari; Ram Chandra Poudel (Nepal Journal of Biotechnology)
A new species of Scleroderma having large sized edible fruiting body, thick peridium and echinulate-spiny spores is identified as Scleroderma yunnanense Y. Wang (Sclerodermataceae, Boletales, Basidiomycota) based on both morphological and Internal Transcribed Spacer (ITS) of nuclear ribosomal DNA sequence analysis. The specimen collected from Pinus patula plantation, in Thaha Municipality of Makawanpur district, Nepal has been described with a discussion on phylogenetic affinities, the global distribution, ecology and ethnomycology.